Thermodynamic parameters of an ultrasound relaxation process in 2-Nitrobutanol-1 - Adam JUSZKIEWICZ; Zofia BARTYNOWSKA-MEUS (Archives of Acoustics, 2016)
Measurements of the velocity and absorption coefficient of ultrasound were carried out in 2-nitrobutanol-1 with respect to the frequency of the sound and the temperature. The relaxation process can be accounted for in terms of a rotation about the C–C bond. The relaxation parameters for the observed process have been determined.